Immobilizing hydroxyapatite microparticles on poly(lactic acid) nonwoven scaffolds using layer-by-layer deposition. Issue 16 (October 2017) - Houdali, Anssar; Behary, Nemeshwaree; Hornez, Jean-Christophe; Vroman, Philippe; Campagne, Christine; Chai, Feng
A composite porous scaffold for bone cell culture was fabricated by immobilizing HA (hydroxyapatite) (Ca10 (PO4 )6 (OH)2 ) microparticles on PLA (poly(lactic acid)) nonwoven fibers using the layer-by-layer deposition technique. A nonwoven PLA of thickness 1 mm, with average pore size of 230 µm and a porosity of 94%, was used. The nonwoven was functionalized with aqueous 65% deacetylated chitosan followed by rinsing, and then a second padding with aqueous sodium alginate loaded with varying percentages of HA microparticles (0.01%, 0.1% and 0.2%), resulting in a composite porous nonwoven. Sodium alginate was revealed to be an efficient polymer for obtaining a stable dispersion of the HA microparticles in an aqueous medium. Atomic force microscopy and scanning electron microscopy images, zeta potential and wettability tests showed successfully the different surface modifications occurring at each step of surface functionalization. The chitosan coating cationized the PLA fiber surface, providing good adhesion of the HA-loaded anionic alginate coating. HA was almost homogeneously distributed at the PLA fiber surfaces with only a small reduction in the scaffold porosity, which reached 75%. The composite PLA/chitosan/alginate/HA nonwoven structures were tested as scaffold for adhesion and proliferation of rat pre-osteoblast MC3T3-E1 cells. The results showed that higher loading with HA improved the MC3T3 cell adhesion and proliferation after 3 and 6 days of culture.